2006
DOI: 10.1185/030079906x96344
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design for the CARDIOVIT Study (Cardiovit, Atherosclerotic vascular disease and hypeRhomocysteinemia:an epiDemiological study in Indians, additionally evaluating the effect of Oral VITamin supplementation)

Abstract: CARDIOVIT is one of the first and largest studies in India to provide insight into the prevalence of hypertHcy, its association with AVD and conventional risk factors and the role of multivitamins in reducing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In agreement with the protective role of selenium a Sweden study performed in 668 elderly subjects showed that persons with serum Se in the lowest quartile had 43% and 56% increased risk for all-cause and cardiovascular mortality, respectively (Alehagen et al 2016). This confirms the reduced incidence of cardiovascular diseases observed in previous studies after supplementation with selenium combined in multivitamins supplements (Czernichow et al 2005;Shenoy et al 2006). There is also evidence that a number of HIV-positive patients suffer from deficiencies in vitamins including selenium (Coodley 1995).…”
Section: Human Studiessupporting
confidence: 82%
“…In agreement with the protective role of selenium a Sweden study performed in 668 elderly subjects showed that persons with serum Se in the lowest quartile had 43% and 56% increased risk for all-cause and cardiovascular mortality, respectively (Alehagen et al 2016). This confirms the reduced incidence of cardiovascular diseases observed in previous studies after supplementation with selenium combined in multivitamins supplements (Czernichow et al 2005;Shenoy et al 2006). There is also evidence that a number of HIV-positive patients suffer from deficiencies in vitamins including selenium (Coodley 1995).…”
Section: Human Studiessupporting
confidence: 82%
“…Population based randomized trials such as CARDIOVIT study,[7] are underway to investigate the association of hyperhomocysteinemia with systemic vaso-occlusive diseases. Until conclusive data is available it is recommended to investigate and treat for hyperhomocysteinemia in cases of vaso-occlusive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reports stating a high prevalence of HHcys in the Indian population are available. [31][32][33][34][35] Young Asian Indian men settled in the United States and Europe have also been reported to exhibit HHcys. 36 -39 In our study, methionine was significantly lower (P ϭ 0.001) in the patients with CRVO, with no significant change in the levels of cysteine and glutathione, showing that there is probably a defect in the transmethylation pathway rather than transsulfuration pathway.…”
Section: Discussionmentioning
confidence: 99%